Implementation of STEM-Based Learning for Strengthening Science Literacy of Students - Sole, Ferdinandus Bele (Jurnal Penelitian Pendidikan IPA, 2021)
This study aims to analyze the STEM approach in learning to strengthen the scientific literacy of students. The method used in this research is qualitative research with data collection techniques, namely literature studies. The data collection method is by reading, identifying, and analyzing, then categorizing, classifying, and describing. In this research, the study of relevant journals, articles, are used to find out how to increase studentsâ€™ science literacy by using STEM in elementary schools.Â Â Based on the results of research, the literature study states that the use of STEM-based learning effectively improves the student’s science literacy. Â The results of the research analysis showed that the results of the pretest scores of students had low concept understanding in the experimental class and the control class. After being given treatment, the results of the posttest scores showed a significant increase in the experimental class